Multiple labels marking connotative values of idioms in the Oxford Idioms Dictionary for Learners of English - Vrbinc, Marjeta; Vrbinc, Alenka (Penerbit Universiti Kebangsaan Malaysia, 2017)
This contribution is aimed at studying multiple labelling in the Oxford Idioms Dictionary for Learners of English (OIDLE2). We sought to establish whether labels belonging to one and the same category combine with one another or whether multiple labelling consists of labels from different categories of labels, the latter providing different types of information. The database used for the analysis was compiled by searching manually through the dictionary and keying in all the idioms with multiple labelling into our database. Altogether, 392 idioms or their senses with two or more labels were found in OIDLE2. The findings of the study are: labels expressing different types of diasystematic information are included; the three most frequent labels appearing in combination with other labels are informal, humorous and old-fashioned; the combination of four labels is used only once, ten idioms were identified with three labels, while the majority of label combinations consist of two labels. The significance of the findings lies in the issues related to multiple labels, combinations of labels expressing different types of diasystematic information and other issues related to labelling in general. The inclusion of diasystematic information largely depends on the type of dictionary and its intended users. This is especially true of dictionaries intended for non-native speakers of a language, where one of the main functions is to promote the active use of a foreign language, and where every single piece of information included in the dictionary counts.